KATA KETERANGAN DALAM BAHASA INGGRIS DAN BAHASA SANGIR DIALEK SIAU (SUATU ANALISIS KONTRASTIF) - SALENDA, CHRISELA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This research is entitled â€œAdverbs in English and in Sangihe language Siau dialect (A Contrastive Analysis)â€. This research attempts to identify, classify, analyzed, and describe the forms and meanings of adverbs in English and in Sangihe language Siau dialect, as well as to contrast them to find out the similarities and differences. The English data were taken from some grammatical books, whereas the data in Sangihe language Siau dialect were taken by some informants who speak Siau dialect well. This research used descriptive method. In this research, the writer used the Concepts of Radford et.al. (2009), Lyons (1975), Frank (1972) and Lado (1971). It was found that English and Sangihe language Siau dialectÂ have similarities and differences.Â The similarities can be found in the forms dan meanings, both language has simple form which is indicating how, where, when, degree, and why. While the differences is adverbs in English language can be formed by adding suffixÂ Â Â Â Â -ly andÂ Â Â -ward(s). While in Sangihe language Siau dialect there is no found that form. Keywords: Adverbs, English and Sangihe language Siau dialect, A ContrastiveÂ Â Â Â Â Â Analysis.